School Organization and Teaching Practices in High Educational Performance Institutions [Organizacio´N Escolar y Trabajo de Ensen&Tild;Anza en Aula de Establecimientos de Alto Desempen&Tild;O Educativo] - Villalta-Paucar, M (Pontificia Universidad Javeriana, 2014)
In this research some of the organizational elements of the school institutional culture are describe as related to teaching practices in institutions with high educational performance in Chile. Mixed methodology is used, two surveys were applied to teachers (N = 60) and Second Year High School students (N = 612), divided into two distinctive areas a) School Institutional Culture and, b) Everyday teaching practices. The contents are analyzed in focal groups with teachers and students. The results lead to the following conclusions: a) a positive correlation exists between the school culture and the teaching techniques; b) there is an agreement in considering that the school organization aims to achieve learning, and; c) discipline in a basic need to implement teaching methodologies in order to achieve learning. Results are discussed.